Diagnostic challenges in Goldenhar syndrome - a case report - Paul Costin Pariza; Vlad Dima; Corina Grigoriu; Costin Berceanu; Tiberiu-Augustin Georgescu; Bianca-Margareta Mihai; Consuela-Madalina Gheorghe; Roxana Elena Bohiltea (Amaltea Medical Publishing House, 2021)
Goldenhar syndrome, also known as oculo-auriculo-vertebral syndrome, represents a rare congenital complex of anomalies, involving the development of the first and second brachial arches during the first embrionary stage. In addition to the craniofacial disorders, Goldenhar syndrome can include central nervous system, heart, skeleton or kidneys pathologies as well as vertebral defects. We present the case of a Goldenhar syndrome whose first pathologic sign was tetralogy of Fallot, with associated cardiovascular disorders (atrial septal defect type ostium secundum, and single umbilical artery) and bilateral microtia, with malformation of auditory canal, mandibular hypoplasia and a single epibulbar dermoid. The Goldenhar syndrome was diagnosed after birth, the article emphasizing the difficulties of prenatal diagnosis.